This is an continuation of the question proof (rule disjE) for nested disjunction
There we learned that
assume "(A ∨ B) ∧ C"
hence "thesis"
proof (elim conjE disjE)
is a nice idiom to resolve such conjunctions.
But what if I, before being able to use elim ...
, need to also apply an introduction rule – say, some induction, or equalityI
. If i try
have "(A ∨ B) ∧ C ⟷ (A' ∨ B') ∧ C'"
proof (rule iffI, elim conjE disjE)
then the elim
only acts on the first goal, the other goal is still noisy with unwanted and easily eliminated operators.
So how do I apply it on all goals introduced by the rule
?